PENGARUH AKUNTANSI KEUANGAN PEMERINTAH DAERAH TERHADAP KUALITAS PENYAJIAN LAPORAN KEUANGAN - Rahman, Fatahul (KOMITMEN: Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the effect of local government financial accounting on the quality of financial reports. The method used in this research is a quantitative method. Based on the research results, it can be concluded that the variables of company management commitment (CMC), human resource competence (HRC), standard operating procedures (SOP), internal control systems, information technology (IT), activity monitoring (AC), and evaluation of activities (EA) both simultaneously and partially affect the quality of presentation of financial statements (QPFS).